OPTIMALISASI KESIAPAN ALAT-ALAT PEMADAM GUNA MENGHADAPI BAHAYA KEBAKARAN DI KM. SABUK NUSANTARA 37 - Rosneli Depita Sari; Rizal Rochmansyah; Bayu Yudho Baskoro; M.Kurniawan; Tri Kismantoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the optimization of the readiness of fire fighting equipment in addressing fire hazards on board KM Sabuk Nusantara 37. The background of this research is based on the importance of fire protection systems on board ships as a preventive and emergency response measure in accordance with international maritime safety regulations. The research employed a descriptive qualitative method. Data were collected through direct observation, interviews with ship officers and crew members, and documentation during sea practice. The data were analyzed using triangulation techniques to obtain valid and objective conclusions. The results of the study indicate that the vessel has been equipped with fire-fighting equipment and Standard Operating Procedures (SOP) in accordance with safety standards. The Portable Fire Extinguishers (PFE) were found to be in good condition, with normal pressure, intact safety seals, and periodic inspections conducted regularly. However, several issues were identified in the fire hose system, including corroded nozzles and damaged or empty hose boxes, indicating that the overall readiness has not yet been fully optimized. The contributing factors include insufficient comprehensive maintenance, the lack of timely replacement of damaged equipment, and the uneven understanding among crew members regarding their duties as specified in the muster list. Optimization efforts include implementing a planned maintenance system, replacing unserviceable equipment, and enhancing crew competence through regular training and periodic fire drills.